Analysis of Social Security Administrators from a Constitutional Law Perspective - Anwar Hidayat (Fox Justi : Jurnal Ilmu Hukum, 2024)
Health services are a human right of every Indonesian citizen as regulated in Law no. 24 of 2011 concerning the Social Security Administering Body (BPJS). The main focus of this research is to analyze the implementation of social security providers within the framework of Indonesian constitutional law. Therefore, this research aims to analyze social security providers in Indonesia which are regulated by Law Number 24 of 2011. This research uses a normative legal approach based on applicable regulations. This research highlights the importance of social security in Indonesia, which is regulated in laws such as the National Social Security System (SJSN) and the Social Security Administering Body (BPJS), as well as amendments to the 1945 Constitution of the Republic of Indonesia. The research findings show that social security is a vital instrument in fulfilling human rights and achieving social welfare for all Indonesian people. The emphasis on social protection and welfare is an integral part of state responsibility, in line with the principles of democracy, rule of law and social justice. It is hoped that through social security, especially for those who are economically vulnerable, such as the poor and underprivileged, it will provide better protection and improve the welfare of society evenly.